Enhanced Photoelectrochemical Water Oxidation Performance by Fluorine Incorporation in BiVO4and Mo:BiVO4Thin Film Photoanodes - Rohloff, Martin; Anke, Bjoern; Kasian, Olga; Zhang, Siyuan; Lerch, Martin; Scheu, Christina; Fischer, Anna (ACS Applied Materials and Interfaces, 2019)
Anion substitution is an emerging strategy to enhance the photoelectrochemical performance of metal oxide photoelectrodes. In the present work, we investigate the effect of fluorine incorporation on the photoelectrochemical water oxidation performance of BiVO 4 and Mo:BiVO 4 thin film photoanodes. The BiVO 4 and Mo:BiVO 4 thin film photoanodes were prepared by a straightforward organometallic solution route involving dip coating and subsequent calcination in air. Fluorine modification was realized by applying a soft and low-cost solid-vapor reaction route involving fluorine-containing polymers and an inert gas atmosphere leading to novel F:BiVO 4 and F/Mo:BiVO 4 thin film photoanodes with substantially increased photoelectrochemical water oxidation properties. Deposition of the cobalt phosphate (CoPi) water oxidation catalyst allowed further enhancement of the photoelectrochemical performance. While Mo doping mainly improves light-harvesting, charge transport, and charge separation efficiencies, F modification was demonstrated to primarily affect the charge transfer efficiency at the semiconductor-electrolyte interface, thereby leading to a photocurrent increase of 40 and 21% upon fluorination of the BiVO 4 and Mo:BiVO 4 photoanodes, respectively, and an applied bias photon-to-current efficiency increase of 35 and 5%, respectively. We thereby could demonstrate that cation and anion co-doping in BiVO 4 as demonstrated for Mo and F allows combining the photoelectrochemically relevant benefits associated with each type of dopant.
CRIS-Team Scopus Importer:2023-03-07
Keywords: bismuth vanadate; fluorination; photoanode; photoelectrochemical water oxidation